Reflexões sobre a prática da educação permanente em saúde no contexto da educação corporativa em uma operadora de saúde - Ester Mendes da Silva (2022)
New education models have emerged to replace traditional training models. The present work has the general objective: To analyze how the Permanent Education in Health (EPS) articulates the Corporate Education in a health operator and specific objectives: To verify the institutional guidelines adopted for the development of people in the organization; Describe the methodologies of the CE education process developed in the organization; Describe the EPS implementation process; Identify the challenges of the EPS process in a health operator; Develop a proposal for Permanent Education for the development of health professionals articulated with EC guidelines. The research approach was qualitative, with an exploratory focus and the method was the case study. The field of investigation was in a health care provider in Belo Horizonte - Minas Gerais. The collaboration of nine participants was obtained for the research, being Health Managers, Human Resources Consultants and Education Analysts. The data collection technique was through a structured interview carried out by the Teams platform. Data analysis followed the content analysis proposals proposed by Bardin, organized into three chronological poles; 1 - the pre-analysis, 2 - the exploration of the material, 3 - the treatment of the results, the inference and the interpretation. In the results after the transcripts and readings of the interviews, the units of contexts and the nuclei of meanings were identified, having as a criterion the thematic proximity of the interview, from which four categories emerged: 1- The organizational logic of planning for the educational process 2 - Challenges of the process of Permanent Education in Health in a health operator 3 - Innovation in the Training Methodology as a management strategy 4 - Reflections on the proposal to implement Permanent Education in Health. In the final elaboration of the work, a technical report was carried out; where some proposed actions were developed for the enrichment of Permanent Education in Health in the structure of a Corporate Education for the development of people in the organization. I concluded that experiencing a work process in a corporate education made it possible to better understand the teaching-learning strategies adopted by the operator, and to understand the needs for changes proposed by people management and thus evolve in the understanding of the institution's educational processes.